2022
DOI: 10.1542/peds.2021-055033
|View full text |Cite
|
Sign up to set email alerts
|

Quality Indicators for Youth Transitioning to Adult Care: A Systematic Review

Abstract: BACKGROUND AND OBJECTIVE: Transition from pediatric to adult care is associated with adverse health outcomes for many adolescents with chronic illness. We identified quality indicators for transition to adult care that are broadly applicable across chronic illnesses and health systems. METHODS: Medline, Embase, and the Cumulative Index to Nursing and Allied Health Literature were searched, covering earliest available date to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 58 publications
0
18
0
1
Order By: Relevance
“…Az egységes ajánlások segítik az individuális intézményi akadályok és a fejlesztést igénylő területek azonosítását [17]. Az átvezetés minőségi indikátorainak kidolgozása napjaink feladata, és fontos, hogy ezek az indikátorok a betegek és gondozóik szempontjait is tükrözzék [18]. Az eddig megnevezett, konszenzus szerinti legfontosabb indikátorok az életminőség, a betegelégedettség, az önhatékonyság, a betegségspecifikus tudás, az adherencia és az átvezetés során "elvesztett" betegek száma [19].…”
Section: Kihívásokunclassified
“…Az egységes ajánlások segítik az individuális intézményi akadályok és a fejlesztést igénylő területek azonosítását [17]. Az átvezetés minőségi indikátorainak kidolgozása napjaink feladata, és fontos, hogy ezek az indikátorok a betegek és gondozóik szempontjait is tükrözzék [18]. Az eddig megnevezett, konszenzus szerinti legfontosabb indikátorok az életminőség, a betegelégedettség, az önhatékonyság, a betegségspecifikus tudás, az adherencia és az átvezetés során "elvesztett" betegek száma [19].…”
Section: Kihívásokunclassified
“…In addition, health care satisfaction and QoL are important aspects to consider when pre‐ and post‐transfer states are compared with each other (Binks et al, 2007; McDonagh, 2007; Nakhla et al, 2008). Furthermore these two constructs were assessed more likely in a study with the context of transition but not within one study, thus, a further investigation of the relation of both constructs could rarely realize (Bailey et al, 2022). Cramm et al (2013) have demonstrated that satisfaction with transitional care before and after the transfer was positively associated with emotional, physical and social domains of health‐related QoL in adolescents with diabetes type 1, juvenile idiopathic arthritis and neuromuscular disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The question however remains what an effective transition program is [9,10]. There is a still ongoing debate in the transition field internationally about how to best evaluate transition programs and what constitutes an effective program [4,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%